2016
DOI: 10.1021/acs.joc.6b02498
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Brønsted Acid-Type Organocatalysis for the Stereoselective Synthesis of Deoxyglycosides

Abstract: A practical approach for the α-stereoselective synthesis of deoxyglycosides using cooperative Brønsted acid-type organocatalysis has been developed. The method is tolerant of a wide range of glycoside donors and acceptors, and its versatility is exemplified in the one-pot synthesis of a trisaccharide. Mechanistic studies suggest that thiourea-induced acid amplification of the chiral acid via H-bonding is key for the enhancement in reaction rate and yield, while stereocontrol is dependent on the chirality of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…While the thiourea itself does not catalyse the glycosylation, it is critical in accelerating the reaction, improving the yields and α/β selectivities. This cooperativity effect was utilized by Galan et al in 2017, where the substrate scope of the glycal addition was expanded towards D -Glucal and L -Rhamnal derivatives when thiourea 4 was used in conjunction with an axial chiral BINOL based phosphoric acid catalyst 23 . Galan et al, Yoshida and Takao et al, as well as Schmidt et al contributed to thiourea catalyzed O and S -glycosylation of 2-nitroglycals 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…While the thiourea itself does not catalyse the glycosylation, it is critical in accelerating the reaction, improving the yields and α/β selectivities. This cooperativity effect was utilized by Galan et al in 2017, where the substrate scope of the glycal addition was expanded towards D -Glucal and L -Rhamnal derivatives when thiourea 4 was used in conjunction with an axial chiral BINOL based phosphoric acid catalyst 23 . Galan et al, Yoshida and Takao et al, as well as Schmidt et al contributed to thiourea catalyzed O and S -glycosylation of 2-nitroglycals 24 26 .…”
Section: Introductionmentioning
confidence: 99%
“…The Schmidt group has successfully applied the synergistic catalysts (thiourea derivatives with phosphorus acids) for stereoselective O -glycoside bond formation [30]. Similarly, Galan et al reported a method for the preparation of 2-deoxyglycosides from glycals under the influence of cooperative catalysis (chiral phosphoric acids/thiourea derivatives) [31]. Encouraged by these reports and our own research interest in developing stereoselective glycosylation methods, we decided to focus our attention on the synthesis of glycosides via cooperative catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…We sought to establish whether the diphenylphosphoric acid generated as a stoichiometric by-product has any effect on the glycosylation reaction. In prior work by Schmidt and coworkers (6,(17)(18)(19), Fairbanks and coworkers (20), Toshima and coworkers (21), Nagorny and coworkers (22,23), Galan and coworkers (24), Bennett and coworkers (25), and others (26,27), phosphoric acids have been shown to be competent catalytic activators in glycosylation reactions involving different types of donors. However, in the model system, addition of exogenous diphenylphosphoric acid was shown to have no detectable effect on either reaction rate or α/β selectivity.…”
Section: Resultsmentioning
confidence: 96%